Improving Turnaround Times for Routine Antimicrobial Sensitivity Testing Following European Committee on Antimicrobial Susceptibility Testing Methodology in Patients with Bacteraemia - Raewyn Edmondson; Kordo Saeed; Steve Green; Matthew O’Dwyer (Antibiotics)
Background/Objectives: Bacteraemia can be fatal without antibiotic intervention. Antibiotic Susceptibility Testing (AST) provides the necessary information for targeted antibiotic therapy; however, the traditional method using disc diffusion can take over two days from a positive blood culture. Inappropriate empiric therapy is associated with increased mortality and increased antibiotic resistance, highlighting the need for more rapid turnaround times for AST. By making changes to an established method, turnaround times can be reduced. Methods: Eighty-two patient positive blood culture samples were collected from January to April 2022, representing the range of common bacteria causing sepsis. This followed the normal methodology in the laboratory of inoculating agar from positive blood cultures in preparation for European Committee on Antimicrobial Susceptibility Testing (EUCAST) disc diffusion AST method. EUCAST methodology outlines that disc diffusion should be performed on isolates from an overnight culture of 16–24 h. This study looked at comparing disc diffusion results from cultures with 6 h of incubation to those with incubation times of 24 h, after organism identification by MALDI-ToF. Results from 6-h and 24-h cultures were compared by disc zone sizes and by interpreted susceptibility reading following EUCAST guidelines of sensitive, resistant, susceptible with increased exposure, or an area of technical uncertainty. Results: A total of 99.65% interpreted susceptibility readings matched across all organisms to all relevant antibiotics, with an average zone size difference of 1.08 mm between results from 6 h versus 24 h cultures. Conclusions: This method offers a non-automated way of using the traditional disc diffusion method, reducing turnaround times while still producing reliable and accurate results. This would mean validated ASTs can be set up in the same day as a blood culture flags positive rather than waiting for a longer culture. As this method is widely used within the laboratory already, it would mean that additional training is not required, as the process is the same, and only incubation time varies. This would positively impact patient outlook due to the shorter use of empiric therapy, and benefit antimicrobial stewardship (AMS).